2020
DOI: 10.1111/bjd.19661
|View full text |Cite
|
Sign up to set email alerts
|

Classification of facial and truncal segmental vitiligo and its clinical courses including recurrence rate and patterns: a retrospective review of 956 patients

Abstract: Zouboulis CC, Nogueira da Costa A, Makrantonaki E et al. Alterations in innate immunity and epithelial cell differentiation are the molecular pillars of hidradenitis suppurativa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Lesion site is another risk factor not only for disease onset but also for disease relapse in vitiligo. A study in patients with SV found that the recurrence rate in facial SV is significantly higher than in truncal SV 11 . Moreover, a prospective study depicted that the face and neck still have better responses compared with the rest of the body even after relapse 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesion site is another risk factor not only for disease onset but also for disease relapse in vitiligo. A study in patients with SV found that the recurrence rate in facial SV is significantly higher than in truncal SV 11 . Moreover, a prospective study depicted that the face and neck still have better responses compared with the rest of the body even after relapse 12 .…”
Section: Discussionmentioning
confidence: 99%
“…A study in patients with SV found that the recurrence rate in facial SV is significantly higher than in truncal SV. 11 Moreover, a prospective study depicted that the face and neck still have better responses compared with the rest of the body even after relapse. 12 Our study confirmed that the face and neck region has…”
Section: Discussionmentioning
confidence: 99%
“…Mono-segmental vitiligo is the most common form of SV, referring to the presence of one or more white depigmented macules distributed on one side of the body, usually respecting the midline (although some lesions may partly cross the mid-line), early follicular involvement (leukotrichia), and rapid development over a few weeks or months, and overall protracted course but secondary extension remains possible in a given segment sometimes years after [ 10 , 11 ]. The aetiology of the SV pattern remains overall elusive.…”
Section: Introductionmentioning
confidence: 99%